IMPACT OF ADVANCED INFORMATION SECURITY MEASURES ON ECONOMIC INFRASTRUCTURE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This paper explores the key aspects of the development of information security technologies and their significant impact on the national economy. In the modern digital era, information security plays a crucial role in ensuring the stability of economic systems, preventing cyber threats, and safeguarding sensitive data. The rapid advancement of digital technologies has led to the emergence of new challenges and risks that necessitate the continuous evolution of security strategies and protective mechanisms. A detailed cross-sectional and comparative analysis has been conducted to evaluate the influence of multiple factors on the efficiency of security management. By integrating advanced security technologies, organizations can improve risk mitigation strategies, enhance data protection measures, and ensure regulatory compliance. The study examines how the adoption of cybersecurity frameworks, encryption technologies, and threat detection systems contributes to the overall resilience of economic infrastructure. The research highlights the role of government policies, industry standards, and corporate investments in shaping the effectiveness of security management practices. By assessing different approaches to security implementation across various sectors, the study provides valuable insights into the best practices for optimizing information security measures. Ultimately, this paper aims to illustrate the necessity of continuous technological innovation in the field of cybersecurity and its direct correlation with national economic growth. The findings emphasize that a well-structured information security strategy is essential for sustaining economic development, protecting digital assets, and fostering trust in digital transactions.